Excerption and inclusion in language and architecture - Lafi, Emad Younis (Iraqi Journal of Architecture and Planning, 2009)
Excerption and inclusion are two terms in Arabi; rhetoric. The excerption is defined as a taking a part oftext from Holly Quran or Hadith and put it in a poem, verse line, or put it in a prose texr. But the Iinguistics expand the concept of this term to include taking from anolher sciences and knowledge, like Grammar, Philology, and Proso.lr,. Inclusion is defined as taking a verse line or part of verse line from another poet to put it in a new poem, it is necessary that the poet who take the text should declare it, and if he hrdes it, it will be plagiarism. This search is use these two terms in iirchitecture, we have now new two terms in architecture, first one; architectural excerption. it means the designer takes a part of religious or historical building and put it in his new design. The designer also can take from another sciences and knowledge, like physics, mathematics. or schools of modern criticism like deconstruction, to put his new design. The second lerm (architectural inclusion) means the designer takes a part of another modem design, neither religious nor historical, if he hides this. it is consi(lered as architectural plagiarism. The search proved that there are many architectural designs lvhich include the nreaning ol these two terms.